2017
DOI: 10.1038/srep43690
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Regional Differences in Sleep Quality and Insomnia: A General Population-based Study in Hunan Province of China

Abstract: Insomnia and the inability to sleep affect people’s health and well-being. However, its systematic estimates of prevalence and distribution in the general population in China are still lacking. A population-based cluster sampling survey was conducted in the rural and urban areas of Hunan, China. Subjects (n = 26,851) were sampled from the general population, with a follow-up using the Pittsburgh Sleep Quality Index (PSQI) for interview to assess quality of sleep and Insomnia (PSQI score >5). While the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
106
9
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 45 publications
22
106
9
5
Order By: Relevance
“…However, Tang et al found that in Hunan province individuals in rural areas tended to report poorer sleep quality than urban residents [19]. The authors attributed this to the higher physical demands of rural work, the presence of older age groups and problems of access to health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Tang et al found that in Hunan province individuals in rural areas tended to report poorer sleep quality than urban residents [19]. The authors attributed this to the higher physical demands of rural work, the presence of older age groups and problems of access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…The above data were obtained from the National Bureau of Statistics [22]. Both area affluence and unemployment have been shown to be associated with SSD but the effect of city size is less conclusive, with some studies suggesting greater sleep deprivation in larger cities [23] while others have suggested that poor sleep quality may be more characteristic of rural areas [19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In German, 36% of the general population slept badly (Hinz et al, 2017). A survey conducted in China reported that the overall prevalence of insomnia was 26.6% among 26,851 subjects from the general population (Tang et al, 2017). A study among 794 medical students in Malaysia found that 16.1% reported bad sleep quality (Zailinawati et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a higher prevalence of poor sleep quality (32.9%) was reported among 1,118 Malaysian tertiary students (Lai, Say, 2013). Shift work, sleep disorders, socioeconomic status, aging, anxiety and the number of chronic disease, amongst others, were found to be significantly associated with poor sleep quality Patel et al, 2010;Luo et al, 2013;Hinz et al, 2017;Tang et al, 2017). Poor sleep quality is often associated with accidents (Garbarino et al, 2001;Powell et al, 2007), and an increased in total healthcare and lost productivity costs (Sarsour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%